Changes in eating habits following total and frontolateral laryngectomy - Pillon, Jackeline; Gonçalves, Maria Inês Rebelo; Biase, Noemi Grigoletto De (São Paulo Medical Journal, 2004)
CONTEXT: Swallowing is a continuous dynamic process, characterized by complex stages, that involves structures of the oral cavity, pharynx, larynx and esophagus. It can be divided into three phases: oral, pharyngeal and esophageal. Dysphagia is characterized by difficulty with, or the inability to swallow food of normal consistencies. OBJECTIVE: To investigate the presence of swallowing difficulties and modifications made to the consistency of the food consumed in cases of total and partial laryngectomy, with or without subsequent radiotherapy, among patients who had not been diagnosed as having dysphagia. TYPE OF STUDY: Descriptive study. SETTING: Voice Clinic of São Paulo Hospital, Universidade Federal de São Paulo/Escola Paulista de Medicina, São Paulo, Brazil. METHOD: 36 laryngectomy patients: 25 total and 11 frontolateral cases, were studied. A survey consisting of a 23-item questionnaire was applied by a single professional. RESULTS: Among those interviewed, 44% reported having modified the consistency of the food consumed (56% of the total and 20% of the partial frontolateral laryngectomy cases). It was not possible to investigate the influence of radiotherapy on the groups in this study, because the partial frontolateral laryngectomy cases were not exposed to radiotherapy. There was a higher incidence of complaints of swallowing difficulties in total laryngectomy cases (p < 0.027) than in partial frontolateral cases. However, there was no relationship between the surgery and weight loss. We also noted the patients’ other problems regarding the eating process, as well as the compensation that they made for such problems. DISCUSSION: Research has shown an association between laryngectomy and swallowing difficulties, although there have been no reports of associated changes in eating habits among laryngectomized patients. CONCLUSIONS: This study showed that difficulty in swallowing is not rare in total and frontolateral laryngectomy cases. Such patients, even those who did not complain of dysphagia, also had minor difficulties while eating, and had to make some adaptations to their meals.